2022
DOI: 10.3389/fonc.2022.951864
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA in cancer drug resistance: Underlying mechanisms and clinical applications

Abstract: Cancer is one of the most frequently diagnosed malignant diseases worldwide, posing a serious, long-term threat to patients’ health and life. Systemic chemotherapy remains the first-line therapeutic approach for recurrent or metastatic cancer patients after surgery, with the potential to effectively extend patient survival. However, the development of drug resistance seriously limits the clinical efficiency of chemotherapy and ultimately results in treatment failure and patient death. A large number of studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 293 publications
0
23
0
Order By: Relevance
“…Noncoding RNAs, such as miRNAs and long noncoding RNAs (lncRNAs), have been found to be promising biomarkers for disease diagnosis or prognosis ( Liu et al, 2022a ; Wang et al, 2022 ; Zhang et al, 2022 ; Zhou et al, 2022 ). Moreover, miRNAs can be targets for the therapeutic drugs.…”
Section: Clinical Potential and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Noncoding RNAs, such as miRNAs and long noncoding RNAs (lncRNAs), have been found to be promising biomarkers for disease diagnosis or prognosis ( Liu et al, 2022a ; Wang et al, 2022 ; Zhang et al, 2022 ; Zhou et al, 2022 ). Moreover, miRNAs can be targets for the therapeutic drugs.…”
Section: Clinical Potential and Future Perspectivementioning
confidence: 99%
“…Cancer compromises human health and results in an economic burden for patients, healthcare systems, and countries. Thus, scientists have been exploring the mechanisms underlying cancer incidence and development ( Liu et al, 2022c ; Zhou et al, 2022 ). Vascular endothelial growth factor-A (VEGFA) is an important factor affecting cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…10−13 circRNAs are characterized by covalent loops that differ from linear RNAs in that they lack the typical 5′ cap and 3′ poly(A) tail of a linear RNA. 14,15 Due to their unique structure and ability to regulate gene expression, circRNAs have gained increasing attention in research in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Noncoding RNAs were originally thought to be nonfunctional. , However, with the development of biological techniques, recent research has shown that noncoding RNAs actually play important roles in gene regulation, development, and other cellular processes. MicroRNAs (miRNAs) can control and modulate the expression of over 60% of coding genes. Long noncoding RNAs are known to be involved in the regulation of the development of various diseases. , circular RNAs (circRNAs) participate in different physiological and pathological processes through much more complicated mechanisms of action. They can affect miRNA and RNA binding protein activity, encode functional proteins, and regulate gene transcription. circRNAs are characterized by covalent loops that differ from linear RNAs in that they lack the typical 5′ cap and 3′ poly­(A) tail of a linear RNA. , Due to their unique structure and ability to regulate gene expression, circRNAs have gained increasing attention in research in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs), such as microRNAs (miRNAs), long noncoding RNAs (lncRNAs), circular RNAs (circRNAs) and small interfering RNAs (siRNAs) are an increasing spectrum of transcriptional regulatory factors with no coding potential but significant structural and regulatory functions (20)(21)(22). MiRNAs are single-stranded RNAs consisting of 20-22 nucleotides, and their primary function is to combine complementary sequences on mRNAs to repress their translation (5).…”
Section: Introductionmentioning
confidence: 99%